2011
DOI: 10.1111/j.1365-2982.2011.01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin‐immunoreactive neurons and mast cells in the mouse esophagus suggest involvement of serotonin in both motility control and neuroimmune interactions

Abstract: The mouse esophagus is endowed with a rich serotonin-positive intrinsic innervation, including enteric co-innervation of striated muscles. Serotonin may modulate vagal motor innervation of esophageal-striated muscles not only at the central level via projections of the raphe nuclei to the nucleus ambiguus but also at the peripheral level via enteric co-innervation. In addition, mast cells represent a non-neuronal source of serotonin, being involved in neuroimmune processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 68 publications
(144 reference statements)
1
25
0
Order By: Relevance
“…In addition, visceral hypersensitivity, which would also explain the frequent overlap between heartburn and irritable bowel syndrome [27] may be caused by psychological factors influencing stimuli processing in the central nervous system (CNS) [28]. Although little is known about the morphological organization of serotonergic neurons in the oesophagus, laboratory and clinical investigations have indicated that serotonin, the main target of both depression and anxiety treatment, plays a role in oesophageal motility [29,30], leading to neurohormonal interaction between the CNS and the gastrointestinal system. On the other hand, it is plausible that the presence of GORD-related symptoms can evoke feelings of depression or anxiety [16] or that there are a subset of patients with co-occurring vulnerability to both mood/anxiety and reflux symptoms [3].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, visceral hypersensitivity, which would also explain the frequent overlap between heartburn and irritable bowel syndrome [27] may be caused by psychological factors influencing stimuli processing in the central nervous system (CNS) [28]. Although little is known about the morphological organization of serotonergic neurons in the oesophagus, laboratory and clinical investigations have indicated that serotonin, the main target of both depression and anxiety treatment, plays a role in oesophageal motility [29,30], leading to neurohormonal interaction between the CNS and the gastrointestinal system. On the other hand, it is plausible that the presence of GORD-related symptoms can evoke feelings of depression or anxiety [16] or that there are a subset of patients with co-occurring vulnerability to both mood/anxiety and reflux symptoms [3].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that some transmitters including serotonin are released from mast cells in the suncus esophagus and that mast cell‐derived components coordinately shorten the esophagus during emesis, contributing to the emetic reflex . In addition, there are serotonergic neurons in the myenteric plexus of the esophagus . These neurons might release serotonin and then induce longitudinal contractions during peristalsis or emesis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have identified serotonin (5-hydroxytryptamine, 5-HT) as one of the putative neurotransmitters involved in esophageal motor function making its receptors suitable therapeutic targets [7]. Studies in healthy volunteers show that acute administration of buspirone, a 5-HT 1 A receptor agonist, has a strong stimulatory effect on esophageal peristalsis and lower esophageal sphincter (LES) function [8, 9].…”
Section: Introductionmentioning
confidence: 99%